2017
DOI: 10.3174/ajnr.a5112
|View full text |Cite
|
Sign up to set email alerts
|

A Multiparametric Model for Mapping Cellularity in Glioblastoma Using Radiographically Localized Biopsies

Abstract: Using localized biopsies, we have generated a model that illustrates a quantitative and significant relationship between MR signal and cell density. Projecting this relationship over the entire tumor volume allows mapping of the intratumoral heterogeneity in both the contrast-enhancing tumor core and nonenhancing margins of glioblastoma and may be used to guide extended surgical resection, localized biopsies, and radiation field mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 27 publications
2
79
0
Order By: Relevance
“…Other work 16 proposed a novel concept of imaging habitats that quantified distinctive tumor sub-regions by its local contrast enhancement, edema, and cellularity in MRI. Moreover, a recent study mearured the relationships between MR signal and cell desity using radiographically localized biopsies 40 , revealing that T2-FLAIR and ADC sequences were inversely correlated with cell density. Table 1 highlights several feature descriptors with their clinical potential.…”
Section: Quantitative Image Feature Extractionmentioning
confidence: 99%
“…Other work 16 proposed a novel concept of imaging habitats that quantified distinctive tumor sub-regions by its local contrast enhancement, edema, and cellularity in MRI. Moreover, a recent study mearured the relationships between MR signal and cell desity using radiographically localized biopsies 40 , revealing that T2-FLAIR and ADC sequences were inversely correlated with cell density. Table 1 highlights several feature descriptors with their clinical potential.…”
Section: Quantitative Image Feature Extractionmentioning
confidence: 99%
“…Nevertheless, it is possible that the BOLD value extracted from the presumed biopsy site could be displaced by Ն1 voxel from the true biopsy location. However, we recently showed that our sampling method has registration accuracy to within ϳ2 mm, 18 suggesting that this type of error would have minimal effect on our results.…”
Section: Figmentioning
confidence: 99%
“…We have recently shown that this method results in spatial accuracy to within ϳ2 mm. 18 Biopsies that were taken from radiologically defined areas of necrosis or those that were predominantly histologically necrotic (Ͼ75% of the tissue sample) were excluded from the analysis.…”
Section: Biopsy Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI and PWI can give some guidance: DWI due to a decrease in the Brownian motion of water molecules if cell density in the tumour is high and PWI attributable to an increase in rCBV due to a pathological neoangiogenesis. [64,101] There is, however, no perfect imaging technique when it comes to identifying non-enhancing infiltrative tumour; histopathology is the gold standard.…”
Section: Paper IImentioning
confidence: 99%